Dinamika psikologis penyintas Pulung Gantung di Gunung Kidul - Budiarto, Sulistyo; Sugarto, Ryan; Putrianti, Flora Grace (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2020)
The high prevalence of suicide rates in Gunung Kidul deserves a scholarly attention, especially through the indigenous perspective. The existence of Pulung Gantung as a cultural myth that endorses suicidal behavior brings about a significant challenge in reducing suicidal rates. The term ‘Pulung’ is understood as a revelation, a sign or a gift, while the word ‘Gantung’ means suspension of a person by a ligature around the neck. Hence, Pulung Gantung is understood as a superstitious revelation that is believed to signal an individual to commit suicide. This study aims to identify the psychological factors that influence pulung gantung phenomenon in Gunung Kidul through phenomenological approach to a suicide survivor and his three close relatives. The results demonstrated that suicidal behavior was explained by the weak protective psychological factors, and that suicidal behavior was not performed as a response to Pulung belief; hence it provides insight to the community that suicidal behavior is preventable. This study could potentially inform the government and related parties to promote suicide prevention in the community